Using songs to improve students’ pronunciation - Nur Laili Rizky Rahmawati; Muhammad Yunus (Journal of Research on English and Language Learning (J-REaLL), 2020)
This research was designed to improve students’ pronunciation at MTs Almaarif 01 Singosari, Malang through songs. In the preliminary study, the researcher found that the students have trouble pronouncing words correctly and confirmed by the result of their English test in oral test that was 57.20. Besides 43 students were taken in VIII A class at MTs Almaarif 01 Singosari, Malang as the sample of the study, this research consists of two cycles; Cycle One with three meetings and Cycle Two with two meetings. In the planning stage, the researcher designed a lesson plan, preparing material, and formulating the criteria of success. The criteria of success that was 70 or more. Additionally, the first result of Cycle One got 63.25. At the final, the result of Cycle Two showed another increase, there were 71.16. In the research finding, it is concluded that the use of songs in teaching pronunciation can improve the pronunciation of the students. All in all, for the teacher should give English songs according to their level; beginner, intermediate, or advanced, for students are suggested to choose other genre of the song for their learning media, such as jazz, rock, and etc. For future researchers are suggested to conduct similar studies on using songs in a different context, subject, or method.